1999
DOI: 10.1021/jm990293a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Erm Methyltransferases from NMR and Parallel Synthesis

Abstract: The Erm family of methyltransferases confers resistance to the macrolide-lincosamide-streptogramin type B (MLS) antibiotics through the methylation of 23S ribosomal RNA. Upon the methylation of RNA, the MLS antibiotics lose their ability to bind to the ribosome and exhibit their antibiotic activity. Using an NMR-based screen, we identified a series of triazine-containing compounds that bind weakly to ErmAM. These initial lead compounds were optimized by the parallel synthesis of a large number of analogues, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 23 publications
1
63
1
2
Order By: Relevance
“…This finding is related to the different interaction points involved in the interaction of tylosin with 23S rRNA, as mentioned previously. Some groups have attempted to design methylase inhibitors able to restore the macrolide activity of bacterial isolates carrying these genes (Hajduk et al, 1999), but no molecule is currently under development for therapeutic use in humans.…”
Section: Methylationmentioning
confidence: 99%
“…This finding is related to the different interaction points involved in the interaction of tylosin with 23S rRNA, as mentioned previously. Some groups have attempted to design methylase inhibitors able to restore the macrolide activity of bacterial isolates carrying these genes (Hajduk et al, 1999), but no molecule is currently under development for therapeutic use in humans.…”
Section: Methylationmentioning
confidence: 99%
“…This strategy can be used when resistance involves antibiotic-inactivating enzymes, and it has been validated with the successful use of β-lactamase inhibitors [17]. A similar approach can be used for target-modifying enzymes [18] and for efflux systems [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported on several potential Erm in- on May 11, 2018 by guest http://aac.asm.org/ hibitors whose actions are based on the ability of the end product of the methylation reaction, S-adenosyl-L-homocysteine, to inhibit the methylation reaction (10,11). These potential inhibitors bind to the active site of the Erm protein, thereby competing with the substrate of the methylation reaction, SAM.…”
Section: Discussionmentioning
confidence: 99%